Creating a Supportive Work Environment: A Cognitive Behavioral Approach for Nurse Leaders - Nurit Zusman; Caryn Scheinberg Andrews; Vladislav Kaslin; Anna C. Kienski Woloski Wruble (Nursing Reports)
Purpose: This article focuses on identifying cognitive behavioral (CB) techniques that can help nurse supervisors more effectively navigate interpersonal challenges, reduce workplace stress, improve team cohesion, and, ultimately, enhance overall organizational performance and staff well-being. Approach: Through a comprehensive review of leadership literature and clinical management practices, we determined that CB techniques could be integrated into nursing management. Two hypothetical scenarios within this context are offered, where CB techniques can enhance nursing leadership effectiveness. Conclusions and Recommendations: CB techniques offer a humanistic approach to nursing leadership through: (1) providing tools for leaders to reframe challenges and frustrations, particularly in resource-limited settings; (2) offering stress-management strategies for nursing leaders; and (3) enhancing communication skills, self-awareness, and team motivation. These applications can potentially improve both staff and management satisfaction, ultimately improving patient care quality. Healthcare organizations should consider incorporating CB techniques into their leadership development programs. We suggest practical ways to implement these techniques in daily nursing management, emphasizing the importance of creating supportive and safe work environments and provide recommendations for future research. This perspective extends the cognitive behavioral approach beyond its traditional therapeutic context into nursing leadership, providing a novel theoretical framework for understanding and enhancing leadership development in healthcare settings.